A study on the relationship between self-concept and student achievement in learning English / Wan Rahanah Khalid - Khalid, Wan Rahanah (2001)
This study attempts to see the relationship between self-concept and student achievement in learning English. This study was carried out at Sekolah Kebangsaan Sentol Patah, Marang, Terengganu. A total of 45 standard 6 students participated in the study. The instruments used in this study were a combination of two sets of questionnaires constructed into two sections A and B. Section A containing questionnaires based on demographic information and section B containing items from Tennessee Self-Concept Scate-TSCS. The data was analysed using SPSSX and to test the hypotheses, Pearson Correlation Test was used. In testing the hypotheses, T-test was used. The result of the study showed that there was no significant relationship between family and physical self-concept and student academic achievement. There was also no significant difference in students’ physical and family self-concept amongst high and low achievers. As a conclusion, it was found that there was no relationship between self-concept and student achievement in learning English.